Influence of Sense of Coherence and Religiosity on Violence Intention among Youth in North-East Nigeria - Fadahunsi, Ayodele Oladele; Fasanmi, Samuel (NIU Journal of Humanities, 2023)
The protracted armed conflict involving Boko Haram, the Nigerian military, and the Multi-National Task Force has given rise to a significant humanitarian crisis in the North-Eastern region of Nigeria. Undoubtedly, the occurrence of violence has led to extensive displacement of individuals, infringements upon international humanitarian and human rights legislation, heightened security risks, and the emergence of a burgeoning humanitarian predicament. It is thus expedient to examine the psychological factors that predispose resident youths to violent intentions and acts. Thus, out of the umpteenth psychological variables that could trigger violent intention, this study examined the influence of sense of coherence, religiosity and gender. It was an ex post facto design where the opinions of eight hundred and sixty-four respondents across the six states of the North-eastern Nigeria were sampled using a battery of standardized tests.  The generated three generated hypotheses were tested using independent t-test. Results revealed that sense of coherence, religiosity and gender played significant roles on the violent intention of the youths in the sampled area. Several recommendations that could stem the tides of violence in the North-Eastern Nigeria were made by the researchers. Keywords: Gender, religiosity, sense of coherence, and violence intention.